IMPACT OF CONSERVATION AGRICULTURE ON SOIL PHYSICAL PROPERTIES IN RICE-WHEAT SYSTEM OF EASTERN INDO-GANGETIC PLAINS - V. Kumar; M. Kumar; S. K. Singh; R. K. Jat (Journal of Animal and Plant Sciences, 2018)
Soils of Indo-Gangetic plains ( IGP) of India are prone to physical degradation due to their low organic matter content, and presence of carbonates, gypsum or other soluble salts. To address these challenges, conservation agriculture ( CA) based crop management practices are being developed. Our objective was to study how CA practices affected soil physical indicators under rice-wheat cropping system. The experiment was carried out in long term ongoing experiment during 2013 (Rice) and 2013-2014 (Wheat) at crop research centre of Dr. Rajendra Prasad Central Agricultural University, India with the aim to compare the impact of conservation agriculture practices on some selected soil physical properties including the soil moisture, soil temperature and root growth of rice and wheat. The experiment was laid out in Randomized Block Design, with seven treatments and three replications. The treatments involved seven combinations of tillage, crop establishment and residue management practices in a rice-wheat rotation - puddled transplanted rice- conventional tillage wheat ( T : PTR-CTW); zero tillage rice-zero tillage wheat on beds having 50% rice residue retained 1 in wheat cycle and 25% wheat residues retained in rice cycle (T : PBZTR-ZTW +RB); zero tillage rice-conventional 2 tillage wheat without residues ( T : ZTR-CTW -R); zero tillage rice-zero tillage wheat without residues (T : ZTR-ZTW - 3 4 R); zero tillage rice-zero tillage wheat having 50% rice residue retained in wheat cycle and 25% wheat residues retained in rice cycle (T : ZTR-ZTW +RB) ; unpuddled transplanted rice-zero tillage wheat with 25% rice residues retained in 5 wheat cycle (T : PuTR-ZTW +RR) ; zero tillage rice with Sesbania aculeata brown manure-zero tillage wheat without 6 residues (T : ZTRBM-ZTW -R). The observations were made in one cycle of rice-wheat cropping after 7-years at three 7 stages i.e., before rice sowing/transplanting, after rice harvest and after wheat harvest. Results revealed that CA practices, zero tillage ( ZT) with or without residues retention significantly improved the soil moisture content ( SMC) and modified the soil temperature (ST) before and after irrigation in both the cropping (P d 0.05) . ZT with or without residues retention significantly reduced the soil bulk density (BD), and improved the air filled porosity (AFP), aggregation (MWD) , water holding capacity (WHC) , hydraulic conductivity (K ) and matric flux potential (Õ) (P d fs m 0.05). Better soil conditions significantly improved root growth of both the crops under CA practices (P d 0.05). The most favourable impact on soil physical properties was observed due to ZT with brown manuring. A positive Polynomial relationship was obtained between soil BD and MWD, WHC and MWD, and K and Õ at all the three stages. Thus, the fs m evaluation of long term CA practices is potentially recommended to different agro-ecologies for their large scale adoption in the north eastern IGP. of mechanical impedance, scarcity of water and high
Keywords: Zero tillage; residues retention; physical properties; root growth; rice; wheat.